Hookworm With Hypereosinophilia: Atypical Presentation of a Typical Disease. Issue 4 (27th May 2013) - Verboeket, Sebastiaan O.; van den Berk, Guido E. L.; Arends, Joop E.; van Dam, Alje P.; Peringa, Jan; Jansen, Rogier R.
Abstract : We describe a 55‐year‐old man returning from the Philippines infected with a hookworm, the novel bacterium Laribacter hongkongensis, and a Blastocystis hominis and presenting with both gastrointestinal and neurological symptoms. The high eosinophilia caused by the hookworm infection resulted in both gastrointestinal and neurological symptoms, resembling a hypereosinophilic syndrome.